The Portrait of Islamic Education Online Learning During the Covid-19 Pandemic in MAN 1 Ternate - Adam, Adiyana; Soleman, Noviyanti (Postgraduate Program, State Islamic Institute (IAIN) Kediri, Indonesia, 2022)
Online learning for Islamic education is an impact of the COVID-19 pandemic. Islamic education is an important subject which contributes to the development of individuals' dignity following the rules and teachings of Islam. However, due to the pandemic conditions, several obstacles affect the effectiveness of online learning for Islamic education. The purpose of the study is to find out how the situation in Indonesia regarding the online learning of Islamic Education, especially in Madrasah Aliyah Negeri 1 Ternate. The researchers tried to answer the problem through the qualitative method and a phenomenological approach deepened through field research. The data used are primary and secondary data taken directly from the field of research, which MAN 1 Ternate and several studies on online learning of Islamic education in Indonesia. The results of the study indicate that the institution in Indonesia does not yet feel the effectiveness of online learning of Islamic education. Meanwhile, it also happened at MAN 1 Ternate, where online learning of Islamic education is not considered adequate yet due to the output as student understanding which is not optimal even the teacher preparation is enough.